The Influence of Price Perception and Delivery Speed on Purchase Decision of Skintific Products and Its Impact on Customer Satisfaction on the Shopee Marketplace in Pontianak City - Nurul Rahmaniah; Sumiyati Sumiyati (SAINTIS Publishing, 2025)
The rapid growth of e-commerce has driven changes in consumer behavior, particularly in purchasing skincare products online. This study aims to analyze the influence of price perception and delivery speed on purchase decisions, as well as their impact on customer satisfaction with Skintific products on the Shopee marketplace in Pontianak City. A quantitative approach with an associative method was employed, involving 100 respondents selected using purposive sampling. Data were collected via questionnaires and analyzed using Structural Equation Modeling (SEM) based on the Partial Least Squares (PLS) method with the assistance of SmartPLS 4.0 software. The results indicate that price perception and delivery speed have a positive and significant influence on purchase decisions. Furthermore, purchase decisions significantly and positively affect customer satisfaction. However, price perception and delivery speed do not have a direct significant impact on customer satisfaction. Indirectly, both price perception and delivery speed show a positive and significant influence on customer satisfaction through purchase decisions as an intervening ariable. These findings highlight the important role of purchase decisions in the relationship between exogenous variables and customer satisfaction. The implications of this study emphasize the importance of competitive pricing strategies and efficient delivery services in enhancing purchase decisions, which ultimately contribute to achieving customer satisfaction in the digital era.